Introduced marine macroflora of Lebanon and its distribution on the Levantine coast - BITAR, G.; RAMOS-ESPLÁ, A. A.; OCAÑA, O.; SGHAIER, Y. R.; FORCADA, A.; VALLE, C.; EL SHAER, H.; VERLAQUE, M. (Mediterranean Marine Science, 2017)
The marine macroflora introduced into Lebanon was studied through an analysis of historical data and field studies carried out since 1991. A total of 29 introduced species have been listed: 3 Chromobionta, 13 Rhodobionta, 12 Chlorobionta and 1 Streptobionta. Among them, Caulerpa taxifolia var. distichophylla, Spatoglossum variabile and Womersleyella setacea are recorded for the first time from Lebanon. Among them, Asparagopsis taxiformis, C. taxifolia var. distichophylla, Cladophora patentiramea, Codium arabicum, Codium parvulum, Galaxaura rugosa, Halophila stipulacea, Hypnea cornuta, Laurencia cf. chondrioides, Lophocladia lallemandii, Stypopodium schimperi, Ulva lactuca and Womersleyella setacea are potentially invasive species, and several of them already occupy extensive stretches of the Lebanese coast. The distribution of species on the Levantine coast, their dynamics and the current status of their populations are discussed.